BRICS Plus dan Restrukturisasi Tatanan Global: Analisis Neo-Realisme, Soft Power, dan Constructivism terhadap Pergeseran Kekuasaan Dunia - Bimo Tri Artomo; Tatok Djoko Sudiarto; Khairizah Khairizah (AKADEMIK: Jurnal Mahasiswa Humanis, 2026)
The expansion of BRICS into the BRICS Plus framework reflects a broader transformation in the global order amid declining Western dominance and the growing assertiveness of emerging economies. While existing studies largely emphasize the economic implications of BRICS enlargement, limited attention has been given to its combined material, normative, and identity-based dimensions. This study aims to analyze how BRICS Plus contributes to the restructuring of the global order by integrating Neo-Realist, Soft Power, and Constructivist perspectives. Employing a qualitative descriptive approach, the research is based on systematic literature analysis of academic journals, policy reports, and official BRICS documents. Data are examined through thematic content analysis to identify patterns related to power balancing, non-coercive influence, and identity construction among BRICS Plus members. The findings indicate that BRICS Plus functions not only as a mechanism of collective balancing against Western-dominated institutions through alternative financial arrangements, but also as a platform for projecting soft power and promoting a shared Global South identity. The study concludes that the influence of BRICS Plus is derived from the interaction between material capabilities, normative appeal, and collective identity formation, positioning it as a significant actor in the ongoing transition toward a more multipolar and inclusive global order.